Africa in Manufacturing Global Value Chains : Cross-Country Patterns in the Dynamics of Linkages - Abreha, Kaleb; Lartey, Emmanuel; Mengistae, Taye; Owusu, Solomon; Zeufack, Albert (World Bank, Washington, DC, 2020)
Africa's linkages in manufacturing global value chains are reasonably high compared with other developing regions. Still, linkage rates have declined steeply in recent years in non-resource rich countries in the region although they have increased sharply in countries that are rich in natural resources. Moreover, the level and dynamics of linkages to manufacturing global value chains vary significantly between countries within each group of natural resource endowments. The current levels, activity structure, and geographic configuration of linkage rates evolved over the past 20 years. In addition, these linkages cut across broad activity categories, including manufacturing textiles and apparel, metal products, transport equipment, and electrical goods. This paper analyzes the sources of the variation in linkage rates in the framework of an estimated gravity and linear probability model. It is shown that the domestic actors in these linkages are typically relatively large establishments (100 or more employees) and have been in operation for five years or longer. These manufacturers are also more likely to have foreign equity holders or foreign technology licenses. These findings should be seen in the light of policies that promote industrialization by facilitating integration into manufacturing global value chains at links that maximize job and productivity gains.